Johannesburg, Ontario: Street Naming Strategies and the Decolonised City to Com - Melissa Levin (The Thinker)
South Af rica’s transition f rom apartheid to democracy was both enabled and burdened by the global political conditions of the late 1980s. The shifting balance of forces at the time meant that the global appetite for authoritarianism was passing as the horizon of possibility suggested by socialism was fading. In other words, democratisation efforts were encouraged by the international community, while radical transformative economic and social projects were not.